The Influence of Trust, Transparency, and Amil Performance on Zakat Receipts with Zakat Digitalization as a Moderator Variable - Nilla Mekar Mawaryani; Nur Kholidah (STAI Al-Mas'udiyah, 2026)
Zakat receipt reflects the effectiveness of zakat management institutions in collecting funds from zakat payer. This study aims to analyze the influence of trust, transparency, and factor performance on zakat receipt at BAZNAS Pekalongan City with zakat digitalization as a mediator variable. This study uses a quantitative strategy through the application of a survey method. Data were collected by distributing questionnaires to zakat payers who channel their zakat funds through the BAZNAS organization in Pekalongan City. The method for analyzing the data involved the use of Partial Least Square–Structural Equation Modeling (PLS-SEM). The research findings indicate that trust, transparency, and the effectiveness of zakat collectors do not have a direct and substantial impact on zakat revenues. However, transparency and amil performance have a significant impact on the zakat digitalization process. In addition, zakat digitalization is proven to have a significant effect on zakat receipt and is able to mediate the effect of transparency and factor performance on zakat receipt, but does not mediate the effect of trust on zakat receipt. These findings indicate that zakat digitalization plays a strategic role in increasing the effectiveness of zakat collection by enhancing the ease, efficiency, and accessibility of zakat services. The implications of this research suggest that BAZNAS (National Agency for Zakat) needs to focus its zakat management strategy on strengthening digital systems supported by transparent fund management and improving the professionalism of amil (collectors). Future research is recommended to include additional variables, such as public understanding of zakat and ease of technology adoption, as well as broaden the scope of research objects.